2019 update to: Management of hyperglycaemia in type 2 diabetes, 2018. A consensus report by the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) - Buse, John B.; Wexler, Deborah J.; Tsapas, Apostolos; Rossing, Peter; Mingrone, Geltrude; Mathieu, Chantal; D’Alessio, David A.; Davies, Melanie J. (Diabetologia, 2020)
The American Diabetes Association and the European Association for the Study of Diabetes have briefly updated their 2018 recommendations on management of hyperglycaemia, based on important research findings from large cardiovascular outcomes trials published in 2019. Important changes include: (1) the decision to treat high-risk individuals with a glucagon-like-peptide 1 (GLP-1) receptor agonist or sodium–glucose cotransporter 2 (SGLT2) inhibitor to reduce major adverse cardiovascular events (MACE), hospitalisation for heart failure (hHF), cardiovascular death or chronic kidney disease (CKD) progression should be considered independently of baseline HbA 1c or individualised HbA 1c target; (2) GLP-1 receptor agonists can also be considered in patients with type 2 diabetes without established cardiovascular disease (CVD) but with the presence of specific indicators of high risk; and (3) SGLT2 inhibitors are recommended in patients with type 2 diabetes and heart failure, particularly those with heart failure with reduced ejection fraction, to reduce hHF, MACE and CVD death, as well as in patients with type 2 diabetes with CKD (eGFR 30 to ≤60 ml min −1 [1.73 m] −2 or urinary albumin-to-creatinine ratio >30 mg/g, particularly >300 mg/g) to prevent the progression of CKD, hHF, MACE and cardiovascular death.